EXPERIMENTAL STUDY OF REINFORCED CONCRETE DAPPED ENDS BEAMS STRENGTHEN WITH TRANSVERSE SUBSEQUENT INSTALLED BARS - Hadi Nasir Ghadhban (Journal of Engineering and Sustainable Development, 2018)
This study involves in taking seven reinforced concrete dapped end beams strengthened with transverse Subsequent installed bars under concentered loads. These specimens of dimension (length=1220 x height=240 x width=130mm) with two types of sections (i.e. without and with transverse opening) and studied to evaluate the response of test beams to compare the strength capacity of beams strengthened with transvers subsequent installed bars relative to beams with or without opening region in sections. All specimens are simply supports. The five of RC dapped ends beams are strengthened with transverses Subsequent installed bars with or without opening and designed to test up to failure. Three parameters were investigated: compressive strength, amount of transvers Subsequent installed bars, and effect of section (with and without opening). It is found that’s increased in compressive strength by about 20% give increase in load carrying capacity by about 9%. Also, the reinforced concrete dapped ends beams contain transverse opening section compared to beams without opening results show decrease in strength capacity and gives more deflection by about in range (10-20%) and (18-26%) respectively. The transverse Subsequent installed bars are provided by steel bolts diameter of 10.5mm gives more enhancement in strength capacity and decrease deflection more than the others without transvers bars by about (8-27%) & (20-30%). Strengthened of beams by transvers bars can show to again in ultimate strength capacity by about (30%).